Utilization of Erythropoietin within the United States Neonatal Intensive Care Units from 2008 to 2017 - Ahmad, Kaashif A.; Bennett, Monica M.; Juul, Sandra E.; Ohls, Robin K.; Clark, Reese H.; Tolia, Veeral N. (American Journal of Perinatology, 2019)
Objective Little data are available regarding erythropoietin (Epo) utilization patterns within neonatal intensive care units (NICUs). We sought to describe the trends in Epo utilization across a large cohort of U.S. NICUs.Study Design This is a retrospective cohort study of infants discharged from 2008 to 2017 using the Pediatrix Clinical Data Warehouse.Results We identified 704,159 eligible infants from 358 sites, of whom 9,749 (1.4%) had Epo exposure. For extremely low gestational age newborns (ELGANs), Epo exposure ranged from 7.6 to 13.5%. We found significant site variability in Epo utilization in ELGANs. Among the 299 NICUs caring for ELGANs during the study period, 184 (61.5%) never used Epo for this population, whereas 21 (7%) utilized Epo in 50% or more of eligible infants. Epo was initiated at a median of 25 days in ELGANs. For infants with hypoxic–ischemic encephalopathy (HIE), Epo exposure remained ≤1% through 2014 then increased fourfold to 3.4% by 2017. The median day of Epo initiation was the day of birth for infants diagnosed with HIE.Conclusion Epo is utilized in ELGANs more commonly than for other NICU populations. Utilization patterns appear to indicate the treatment of established anemia for ELGANs and more recently for neuroprotection in patients diagnosed with HIE.
Keywords: erythropoietin; hypoxic–ischemic encephalopathy; neuroprotection; prematurity; ELGAN